1992
DOI: 10.1152/ajpheart.1992.262.5.h1579
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelium-derived relaxing factor in parasympathetic coronary vasodilation

Abstract: Vasodilation following the infusion of acetylcholine is due to the release of endothelium-derived relaxing factor (EDRF). However, the role of EDRF in neurogenic coronary vasodilation, when acetylcholine is released outside the vessel at the adventitial-medial junction, has not been established. The action of EDRF in parasympathetic coronary vasodilation was tested in the present study using a specific inhibitor of EDRF synthesis, nitro-L-arginine methyl ester (L-NAME). Experiments were conducted on closed-che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 0 publications
5
66
0
Order By: Relevance
“…NO is involved in vagally mediated pulmonary (18) and coronary vasodilation (19), and in nonadrenergic, noncholinergic neurotransmission in animals (20,21) and humans (22,23 Experimental protocols Intracoronary dobutamine. Animals were allowed to stabilize for 30 min after instrumentation.…”
Section: -Adrenergic Agonistmentioning
confidence: 99%
See 1 more Smart Citation
“…NO is involved in vagally mediated pulmonary (18) and coronary vasodilation (19), and in nonadrenergic, noncholinergic neurotransmission in animals (20,21) and humans (22,23 Experimental protocols Intracoronary dobutamine. Animals were allowed to stabilize for 30 min after instrumentation.…”
Section: -Adrenergic Agonistmentioning
confidence: 99%
“…The intraaortic balloon was inflated in a graded fashion with an inflation device (model SM 2500; SciMed, Maple Grove, MN) to maintain BP within 10 mmHg at a given dobutamine dose with and without vagal stimulation. Inhibition of NOS was achieved by intracoronary infusion of NG-monomethyl-L-arginine (L-NMMA; CalbiochemNovabiochem Corp., La Jolla, CA) at a rate of 10 ,umol/min which yields a coronary concentration of 100 MM, assuming a total left coronary flow of 100 ml/min (19). After a 20-min infusion of L-NMMA and during concurrent administration of L-NMMA, vagal nerve stimulation was repeated without and with intracoronary infusion of dobutamine.…”
Section: -Adrenergic Agonistmentioning
confidence: 99%
“…It has nevertheless been suggested that acetylcholine released from parasympathetic adventitial nerves diffuses to the endothelium in concentrations sufficient to stimulate NO synthesis in the coronary and pulmonary circulations, on the basis that vasodilatation induced by vagal stimulation is blocked not only by atropine, but also by L-NAME (Broten, Miyashiro, Moncada & Feigl, 1992;McMahon, Hood & Kadowitz, 1992). This point requires further evaluation, however, as the effects of subsequent administration of L-arginine were not tested, and L-NAME and other alkylated esters of L-arginine may irreversibly bind to MI, M2 and M3 muscarinic receptors (Buxton, Cheek, Eckman, Westfall, Sanders & Keef, 1993).…”
Section: Flow-induced Release Of Endothelium-dependent Agonistsmentioning
confidence: 99%
“…NO is recognized as a major endothelium-derived relaxing factor (1), and has been shown to participate in parasympathetic coronary vasodilation (2,3) and in inhibition of sympathetic peripheral and coronary vasoconstriction (4,5). NO has been shown to modulate myocardial contractility in response to both cholinergic (6, 7) and ␤ -adrenergic (8) stimulation.…”
Section: Introductionmentioning
confidence: 99%